CD103−CD11b+ dendritic cells regulate the sensitivity of CD4 T cell responses to bacterial flagellin - Atif, Shaikh M. (2013)
Toll-like receptor 5 (TLR5) has been widely studied in an inflammatory context, but the effect of TLR5 on the adaptive response to bacterial flagellin has received considerably less attention. Here, we demonstrate that TLR5 expression by DCs allows a 1000-fold enhancement of T cell sensitivity to flagellin, and this enhancement did not require the expression of NLRC4 or Myd88. The effect of TLR5 on CD4 T cell sensitivity was independent of the adjuvant effect of flagellin and TLR5 ligation did not alter the sensitivity of OVA-specific T cells to OVA. In the spleen, the exquisite T cell sensitivity to flagellin was regulated by CD4−CD8α− dendritic cells and was blocked by a monoclonal antibody to TLR5. In the mesenteric lymph nodes, flagellin-specific T cell activation was regulated by a population of CD103−CD11b+ DCs. Thus, TLR5 expression by mucosal and systemic DC subsets controls the sensitivity of the adaptive immune response to flagellated pathogens.